Three-dimensional biological hydrogel as well as preparation method and application thereof
By using a three-dimensional biohydrogel scaffold at joint cartilage defects or lesions, combining nano-level liposomes and stem cell solutions, a superlubricated biological microenvironment is solved, and the problem of difficulty in fundamentally repairing articular cartilage in the existing technology is solved, achieving long-term and stable cartilage repair and pain relief effects.
Patent Information
- Application Number
- CN202411860016.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-17
AI Technical Summary
The prior art is difficult to fundamentally repair and cure defects and lesions of articular cartilage, and conventional injection methods have problems such as low accuracy, multiple side effects and short therapeutic effects.
A three-dimensional biohydrogel is used, and its raw materials include methacrylic anhydride hyaluronic acid, initiator, hydrogenated soybean phosphatidylcholine liposomes and stem cell solutions. Gelatin microspheres are prepared through microfluidic control technology, and nano-level liposomes are introduced into the hydrogel scaffold to construct a superlubricated biological microenvironment, promote stem cells to differentiate into chondrocytes and secrete extrachondrocyte matrix.
It has achieved fundamental repair and cure cartilage in joint defects or lesions, which has significant clinical significance and can relieve pain and repair cartilage in a long and stable manner, which is far superior to existing market products.
Smart Images

Figure HDA0005192969860000011 
Figure HDA0005192969860000012 
Figure HDA0005192969860000021
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of joint repair hydrogels, and in particular to a three-dimensional biological hydrogel and a preparation method and application thereof. Background Art
[0002] Stem cell therapy has always been a hot topic in tissue repair and clinical treatment. In particular, stem cells have the ability to differentiate into different types of cells, which gives them considerable application prospects and potential in various fields. However, precisely because of their ability to differentiate in multiple directions, if there is no suitable growth environment, stem cells are also very likely to differentiate in unexpected directions, thereby losing the expected repair and treatment effects, and may even cause side effects. Hydrogel (Hydrogel), because it is similar to human tissue components and has long been proven to have good biocompatibility, hydrogel scaffolds have also begun to play an important role in tissue engineering. With the exploration of the potential and market demand for stem cell therapy, by designing and constructing three-dimensional hydrogel scaffolds with specific biological microenvironments, stem cells are induced to achieve directional differentiation, growth, and proliferation, and then the repair effect is achieved in defective tissues or lesions.
[0003] Lacuna is a unique structure of chondrocytes in natural joint tissue and three-dimensional culture (such as Figure 1 Because of this characteristic, chondrocytes tend to grow independently under three-dimensional growth conditions, forming a round / elliptical structure with a layer of cavities, unlike the long spindle shape that is attached to the substrate during two-dimensional culture. According to existing relevant literature, the radial size of the cavities is also directly related to osteoarthritis (OA). Studies have shown that under OA conditions, the size of the cavities around chondrocytes will also increase, significantly increasing from 30-50um in healthy cartilage cavities to an average of 100μm and above in OA diseased cartilage cavities ( Figure 1 A and 1B) [3] .
[0004] In addition, according to literature, when bone marrow-derived mesenchymal stem cells (BMSCs) are cultured in a three-dimensional bioscaffold with cell adhesion ligands / strong adhesion, the bioscaffold can support the mechanical conduction of the loaded cells and promote the differentiation of stem cells into osteoblasts; on the contrary, in a bioscaffold without cell adhesion ligands / weak adhesion, it can support the proliferation of stem cells into spheres and the formation of a hypoxic microenvironment, so that they are more likely to differentiate into chondrocytes when cultured in this independent nesting state in three dimensions. [4,5]According to a paper published in Advanced Materials by Ming-Zhu Zhang's team in 2023, it was verified that when chondrocytes are cultured in three dimensions in hydrogels and are subject to the geometric constraints provided by the microenvironment, they can further promote the secretion of more extracellular matrix (ECM) by chondrocytes, such as proteoglycans and glycosaminoglycans (GAGs), and significantly inhibit the hypertrophy and dedifferentiation of chondrocytes. [3] .
[0005] Natural articular cartilage has a strong lubricating effect, and its friction coefficient COF (Coefficient of friction) can reach 0.002-0.02 [6] At present, there are few technologies that can produce artificial materials with such super-lubricating effects. In addition to our daily lives, the lubrication mechanism of articular cartilage also plays an indelible role in early osteoarthritis (OA) and cartilage repair. It has been documented that in early OA, due to the increase in COF, chondrocytes are stimulated by greater shear stress, thereby secreting more matrix degrading enzymes, such as MMP13 and ADAMTS. [5-7] It is proposed that repairing cartilage tissue from the perspective of lubrication mechanism in the joint is a new and effective perspective and potential method. Among them, the boundary layer effect is one of the main lubrication mechanisms of natural articular cartilage. The boundary layer effect is a kind of intermolecular force that realizes the lubrication function through the "hydration shell effect" mechanism, such as Figure 2 shown.
[0006] When a highly polar central molecule appears in an aqueous solution, it attracts surrounding water molecules to form a structure similar to a "water shell". Because this structure is very stable, when the formed water shell is squeezed and deformed by the outside world, other surrounding water molecules will immediately replenish it to maintain the structural and functional stability of the water shell. The whole process takes about 10 -9 seconds, so the energy loss generated is negligible, and energy loss is the most concentrated form of performance in the friction process. The emergence of the water shell effect can reduce energy loss in the application environment, such as extrusion and wear, thereby greatly improving the lubrication effect. [8,9] .
[0007] In order to solve the problem of how to restore the super-lubricating ability of natural cartilage, at the end of 2020, Professor Jacob Klein's team from Israel discovered that after preparing phospholipid molecules into liposomes and then introducing them into a certain three-dimensional hydrogel scaffold, they could successfully use the boundary layer effect to make the hydrogel scaffold reach the COF of natural cartilage, and published this part of the work in the form of a paper in the journal Science.
[10] As we all know, phospholipid molecules are composed of a hydrophilic end at the head and a hydrophobic end at the tail. It is precisely because of this special structure that the head of phospholipids has a strong polarity and can attract the aggregation of water molecules. Liposomes are spherical molecules (such as nanometer-scale) formed by phospholipids through microfluidics, extrusion or ultrasound. Figure 3 A), because its outer layer is all hydrophilic structure, and the hydrophobic end is wrapped in the ball, so that the hydrophilicity and polarity of the liposome are greatly enhanced. Liposomes themselves can be divided into multilamellar large vesicles (MLV), large unilamellar vesicles (LUV), and small unilamellar vesicles (SUV) according to their particle size (as shown in Figure 3 B) and other types, and have a larger specific surface area, which can further enhance polarity and hydrophilicity.
[0008] It is precisely because of such epoch-making theoretical and experimental basis that super-lubricating hydrogels are full of prospects in the application of cartilage repair and clinical treatment.
[0009] However, the current commercial products and technologies for cartilage repair mainly include:
[0010] 1. AqueousJoint [1] :
[0011] AqueousJoint is a product launched by Liposphere. The product uses the boundary layer lubrication effect as a lubrication mechanism to form an ultra-low friction interface within the joint and act as a boundary lubricant. In terms of efficacy, it claims to have unique biolubrication properties, especially in high-pressure and heavy-loaded primary synovial joints.
[0012] Application:
[0013] This product is mainly injected into the joint cavity to achieve the effect of relieving pain and preventing it.
[0014] Possible problems (deficiencies):
[0015] 1) Application method:
[0016] The traditional injection method is used, which is prone to inaccurate injection position; and the traditional injection method also has the risk of pain, swelling and fluid accumulation;
[0017] 2) Potential risks are unknown:
[0018] The product only passed clinical review at the end of 2022 and has just been launched on the market. There is little market feedback and it is still unknown whether there are potential risks;
[0019] 3) High price;
[0020] 4) Product effect:
[0021] The current positioning of this product is rather vague, and it is mainly focused on preventing and relieving joint pain. Whether it can completely repair and treat joint diseases such as joint defects and osteoarthritis, the effect and duration are still unknown.
[0022] 2.Durolane [2] :
[0023] Durolane is a single-injection hyaluronic acid (HA) treatment indicated for the relief of pain associated with knee osteoarthritis and for providing joint lubrication.
[0024] Durolane's mechanism of action is primarily based on hyaluronic acid (HA) injections, which involve multiple factors, such as mechanical lubrication and protection of joints, covering sensory nerve endings, binding to molecules of pain mediators, and possibly playing a nutritional metabolic role within the joints.
[0025] 1) Application method:
[0026] As with the former, it is injected into the articular cavity.
[0027] 2) Possible problems (shortcomings):
[0028] Common side effects include pain, swelling, warmth, redness, and / or fluid at the injection site. Serious side effects are rare but may include allergic reactions, infections, and bleeding into joints.
[0029] Research has found that the half-life of this product in the rabbit knee joint is about 32 days. There is currently a lack of detailed data in the human body (also subject to individual differences). If rabbit samples are used as a reference, the product lasts for a short time and requires long-term injections, which will cause inconvenience to customers' lives and also bring a greater economic burden.
[0030] 3. Platelet-Rich Plasma (PRP) therapy:
[0031] Platelet-rich plasma (PRP) therapy is a form of regenerative medicine that uses components of a patient's own blood to promote healing, particularly in damaged tissues such as cartilage. However, PRP is not sold as a branded "product" like a drug or medical device; rather, it is a procedure performed in a clinical setting. The process involves taking a sample of the patient's blood, concentrating the platelets and growth factors through centrifugation, and then injecting this concentrated mixture into the site of injury to promote healing and repair. Currently, several biomedical companies have the technology to provide PRP treatments.
[0032] 1) Principle:
[0033] PRP primarily uses the patient / client’s own blood components to repair and heal joints, which can significantly reduce inflammatory responses.
[0034] 2) Application method:
[0035] The injection method is similar, but the preparation process requires blood to be drawn from the patient and processed to concentrate the platelets before injection.
[0036] 3) Possible problems (shortcomings):
[0037] Because it comes from the patient's own blood, side effects are generally fewer, but the risks associated with the injection still exist.
[0038] In summary, it is not difficult to find that most of the existing related technologies and products currently use intra-articular injection to improve the intra-articular environment through drug products / self-plasma to prevent and relieve pain. Although this type of effect is relatively conservative and simple to operate, it cannot be accurately positioned and is prone to side effects such as pain and swelling at the injection site; in addition, it is well known that articular cartilage itself does not have the ability to repair, and most of the above products only have a short-term effect of relieving pain and improving the internal environment. The root cause of the disease has always existed and cannot be completely eliminated; and most drugs exist in the joint cavity in the form of liquid, and their stability is poor, and long-term effectiveness cannot be guaranteed. Customers / patients need to be injected regularly for a long time to maintain, which seriously affects the quality of life and also causes great economic pressure.
[0039] Prior art CN114146226A discloses a bone marrow mesenchymal stem cell / degradable hydrogel composite material and its preparation method and use. The material uses polyethylene glycol derivatives and active oxygen responsive small molecule diamines as raw materials to prepare polyethylene glycol hyperbranched polymers containing active oxygen responsiveness as components of the hydrogel, hyaluronic acid modified by methacrylate as another component, cell adhesion peptides, basic fibroblast growth factor and epidermal growth factor as biologically active ingredients, and bone marrow mesenchymal stem cells are loaded therein, and prepared by a method of cross-linking gelation induced by ultraviolet light radiation. However, the prior art introduces cell adhesion peptides, which causes mesenchymal stem cells to tend to attach and grow, which is completely different from the independent / suspended growth mode of cartilage differentiation and cannot be used for cartilage differentiation applications.
[0040] Prior art CN115501253A discloses a preparation of a combined stem cell and hydrogel biomaterial and its application in spinal cord injury, characterized in that it includes the following steps: preparing methacrylated gelatin (GelMA) and methacrylated hyaluronic acid (HAMA); preparing a hydrogel solution, combining standard cultured mesenchymal stem cells or / and neuroepithelial stem cells and encapsulating them in the prepared hydrogel to obtain stem cell-loaded hydrogel or hydrogel microspheres; transplanting the stem cell-loaded hydrogel or hydrogel microspheres to the spinal cord injury for treatment and evaluating the effect. This invention is used to repair spinal cord injury, uses biomaterials, has low immunogenicity, has good cell biocompatibility, and has certain biological functions; after transplantation, it can reduce the excessive aggregation of astrocytes after spinal cord injury, reduce the formation of glial scars, improve bladder and motor function, promote the regeneration and repair of nerves after spinal cord injury, and then promote the behavioral recovery of animals with spinal cord injury.
[0041] Prior art CN118178734B discloses a preparation method and application of a 3D composite hydrogel loaded with stem cells, which belongs to the technical field of wound repair hydrogels. The preparation method includes: S1, preparing GelMA micro-hydrogel by microfluidics; S2, preparing an aqueous solution with a total mass concentration of HAMA and GelMA of 3wt%-8wt%, adding 10-100 freeze-dried GelMA micro-hydrogels to the aqueous solution of HAMA and GelMA, adding 0.5wt%-3wt% phenyl (2,4,6-trimethylbenzoyl) lithium phosphate, shaking and mixing to obtain a composite solution; S3, taking 100μL-300μL of a concentration of 1×10 6 mL -1 -5×10 6 mL -1The stem cell suspension is added to the composite solution obtained in step S2, and the mixture is shaken and mixed; the solution is transferred to a silicone mold, and a 3D composite hydrogel loaded with stem cells is formed by photocuring. The invention discloses a preparation method and application of a 3D composite hydrogel loaded with stem cells, wherein GelMA micro-hydrogel and stem cells are loaded into HAMA-GelMA hydrogel, and the growth of stem cells in a 3D hydrogel environment is regulated by the degradation of GelMA micro-hydrogel. However, the prior art is used for skull repair, which belongs to the repair of osteoblasts.
[0042] GelMA micro-hydrogels are used in both of the above technologies and participate in the three-dimensional culture of stem cells and the entire repair process. GelMA is the full name of methacrylic anhydride gelatin, which is modified from natural gelatin (Gelatin)
[11] In GelMA, stem cells tend to grow by adhering to the wall, which promotes their differentiation into osteoblasts or neurons. However, adhering to the wall is not conducive to cartilage differentiation and cartilage repair. Therefore, the above two existing technologies are not suitable for cartilage repair.
[0043] References:
[0044] 1.Liposphere.Company-Liposphere.Available from:https: / / www.lipo-sphere.com.
[0045] 2.DUROLANE.DUROLANE-Durolane.Available from:https: / / durolane.com / en / durolane / .
[0046] 3.Ding, SL, et al., Cartilage Lacuna-Inspired Microcarriers DriveHyaline Neocartilage Regeneration. Adv Mater, 2023.35(30):p.e2212114.
[0047] 4. Yang, B., et al., Enhanced mechanosensing of cells in synthetic 3D matrix with controlled biophysical dynamics. Nature Communications, 2021.12(1):p.3514.
[0048] 5.Yang,X.,et al.,Coacervation-Mediated Cytocompatible Formation ofSupramolecular Hydrogels with Self-Evolving Macropores for 3D MulticellularSpheroid Culture.Adv Mater,2023.35(24):p.e2300636.
[0049] 6.Radin,E.L.,D.A.Swann,and P.A.Weisser,Separation of a hyaluronate-free lubricating fraction from synovial fluid.Nature,1970.228(5269):p.377-8.
[0050] 7.Lin,W.and J.Klein,Recent Progress in Cartilage Lubrication.AdvMater,2021.33(18):p.e2005513.
[0051] 8.Goldberg,R.,et al.,Boundary lubricants with exceptionally lowfriction coefficients based on 2D close-packed phosphatidylcholineliposomes.Adv Mater,2011.23(31):p.3517-21.
[0052] 9.Jahn,S.,J.Seror,and J.Klein,Lubrication of Articular Cartilage.AnnuRev Biomed Eng,2016.18:p.235-58.
[0053] 10.Lin,W.,et al.,Cartilage-inspired,lipid-based boundary-lubricatedhydrogels.Science,2020.370(6514):p.335-338.
[0054] 11.Van Den Bulcke,AI,Bogdanov,B.,De Rooze,N.,Schacht,EH,Cornelissen,M.,&Berghmans,H.(2000).Structural and rheological properties ofmethacrylamide modified gelatin hydrogels.Biomacromolecules,1(1),31-38.https: / / doi.org / 10.1021 / bm990017d Summary of the invention
[0055] The purpose of the present invention is to provide a three-dimensional biohydrogel that can fundamentally repair and heal articular cartilage, and a preparation method and application thereof.
[0056] In order to achieve the above object, the technical solution of the present invention is as follows:
[0057] A three-dimensional biohydrogel, whose raw materials include, by weight: 1-5 parts of methacrylic anhydride hyaluronic acid HAMA, 0.05-0.15 parts of initiator, 3-8 parts of hydrogenated soybean phosphatidylcholine liposomes and 7-13 parts of stem cell solution;
[0058] The preparation method of the stem cell solution comprises: mixing gelatin and water to prepare a gelatin solution; stirring the mixture at 40-60° C. to prepare a dispersed phase; adding an emulsifier to the oil to prepare a continuous phase; preparing the dispersed phase and the continuous phase to obtain uniform droplets through microfluidics technology, freeze-drying the droplets to obtain gelatin microspheres; adding 5*10 5 / mL of stem cells, incubate at 25-37°C for 2-4h to obtain a stem cell solution.
[0059] The density of stem cells was calculated based on the volume of the stem cell solution.
[0060] Methacryloylated hyaluronic acid (HAMA) serves as the main part of the hydrogel scaffold; hydrogenated soybean phosphatidylcholine (HSPC) liposomes serve as important lubricating units in the hydrogel scaffold; gelatin microspheres adhere to the cells in the three-dimensional scaffold and degrade into artificial cavities during the subsequent cultivation process, restoring the growth environment of natural chondrocytes.
[0061] In the present invention, the three-dimensional biohydrogel is attached to the joint defect or the diseased part. In the early stage, the high biocompatibility and biological fit of the hydrogel are used to achieve the effect of artificial natural articular cartilage, which can relieve the patient's pain and inhibit the deepening of the disease; in the middle and late stages, because the three-dimensional hydrogel scaffold provides a very favorable growth and differentiation environment for stem cells, when the scaffold gradually degrades with the incubation of cells, the stem cells also differentiate into chondrocytes and secrete rich cytoplasmic extracellular matrix to fill the joint defect, thereby repairing and healing the articular cartilage from the root. The present invention can restore the growth microenvironment of chondrocytes, thereby further promoting the differentiation of mesenchymal stem cells towards the cartilage phase, and secreting more cartilage cell extracellular matrix, such as type II collagen and polysaccharide protein, etc., in the subsequent growth process, thereby improving the repair ability of articular cartilage.
[0062] In a preferred embodiment, the stem cells are any one of mesenchymal stem cells and induced pluripotent stem cells.
[0063] In one preferred embodiment, the mass concentration of gelatin in the gelatin solution is 8%-15%.
[0064] In a preferred embodiment, the oil is mineral oil or vegetable oil.
[0065] In a preferred embodiment, the emulsifier is Tween 80.
[0066] In one preferred embodiment, the mass ratio of the oil to the emulsifier is 95-99:1-5.
[0067] In one preferred embodiment, the volume ratio of the continuous phase to the dispersed phase is 5-10:1.
[0068] In one preferred embodiment, in the process of preparing uniform droplets by microfluidic technology, the flow rate of the dispersed phase is 30-40 μL / min; and the flow rate of the continuous phase is 500-600 μL / min.
[0069] Too high or too low a flow rate will result in uneven and unstable droplet sizes.
[0070] In a preferred embodiment, the droplets are freeze-dried and then washed with ethanol or water before freeze-drying.
[0071] In one preferred embodiment, the freeze-drying temperature is -40 to -20°C, the vacuum degree is below 200 Pa, and the time is 18-24 hours.
[0072] In one preferred embodiment, the particle size of the gelatin microspheres is less than 65 μm.
[0073] The gelatin microspheres prepared by the microfluidic method of the present invention can have their diameter controlled to be less than 65 μm, and the size of the "artificial cavity" left after the gelatin degradation can be made to fit the growth microenvironment of normal chondrocytes; 60 μm is a cavity size that is very close to and fits normal chondrocytes. If the particle size of the gelatin microspheres is too large, the cavity formed subsequently will be closer to the cavity size of hypertrophic chondrocytes (chondrocytes with OA lesions), and it is easy to restore the cell microenvironment of the lesion or inflammatory state. The present invention uses gelatin as a hydrogel to form a microsphere morphology through a process, and controls it to fit the ideal size of normal chondrocytes. On the other hand, the gelatin microspheres of the present invention will degrade rapidly at physiological temperature, and can leave an "artificial cavity" suitable for stem cells to differentiate into cartilage phase in the early stage.
[0074] In one preferred embodiment, the particle size of the gelatin microspheres is 40-60 μm.
[0075] Based on the same inventive concept, the present invention also claims a method for preparing the three-dimensional biohydrogel, comprising the following steps:
[0076] S1, adding an initiator to methacrylic anhydride hyaluronic acid HAMA to obtain a hydrogel precursor solution;
[0077] S2. Add hydrogenated soybean phosphatidylcholine liposomes and stem cell solution to the hydrogel precursor liquid, mix well, and obtain a composite solution; transfer the solution to a mold, and form a three-dimensional biohydrogel by photocuring.
[0078] In one preferred embodiment, the preparation method of the methacrylic anhydride hyaluronic acid HAMA is:
[0079] In a dark environment, equal masses of methyl methacrylate and hyaluronic acid are mixed evenly on ice, reacted for 10-14 hours, and the pH is maintained at 8-8.5. The obtained solution is dialyzed and freeze-dried to obtain methacrylic anhydride hyaluronic acid HAMA.
[0080] In a preferred embodiment, the molecular weight of the hyaluronic acid is 100,000-200,000.
[0081] In one preferred embodiment, the dialysis process is: transferring the solution into a dialysis bag with a molecular weight cutoff of no more than 20 kDa, and dialysis in water for 1-3 days.
[0082] In a preferred embodiment, hydrogenated soybean phosphatidylcholine liposomes are first dispersed and then added dropwise into the hydrogel precursor solution.
[0083] In one preferred embodiment, the process of dispersing hydrogenated soybean phosphatidylcholine liposomes is: ultrasonically dispersing hydrogenated soybean phosphatidylcholine liposomes in water, with an ultrasonic frequency of 600-700W and an ultrasonic time of 10-20min to hydrogenate the soybean phosphatidylcholine liposomes.
[0084] In one preferred embodiment, the light curing is performed at 365 nm, 8 mW / cm 2 -12mW / cm 2 Curing under blue light for 4-8 minutes.
[0085] In one of the preferred embodiments, the mold is obtained by performing a CT scan on the patient's articular cartilage defect, and the scan result is imported into a 3D bio-printing machine to generate a corresponding printing model and parameters to obtain a mold.
[0086] Based on the same inventive concept, the present invention also claims to protect the use of the three-dimensional biohydrogel in preparing a preparation for cartilage repair.
[0087] In the present invention, nano-scale liposomes will be constructed and implanted into a three-dimensional hydrogel scaffold, which will greatly improve its lubrication properties from the perspective of material characterization, approaching or even reaching the COF level of natural cartilage (about 0.002-0.02); from the perspective of physiological function, when cells are cultured three-dimensionally in super-lubricating hydrogels, the superior lubrication effect reduces the shear stress stimulation to the cells, thereby down-regulating the gene expression and protein secretion of MMP13, ADAMTS 5 and type X collagen (Col X) that lead to cell hypertrophy and matrix degradation, and because the three-dimensional environment is more consistent with the superficial layer (Superficial layer) of natural articular cartilage, the gene expression of Proteoglycan4 (PRG4) linked to lubricin in chondrocytes is up-regulated, and a chemical substance in the matrix that has a lubricating effect, Lubricin, is secreted, thereby better matching the biological microenvironment of cartilage, achieving the expected cartilage repair and clinical treatment effects.
[0088] According to some basic cell and animal experimental data we have, Figure 4-9), when the cells were cultured in the super-lubricating hydrogel we constructed in three dimensions, they not only showed high biocompatibility, but also, compared with the material control group, the various cartilage indices of the cells in the super-lubricating hydrogel were significantly improved, such as secreting more extracytoplasmic matrix (ECM), and the repair effect was more obvious in the osteochondral defect model. Not only did the expression of PRG4 in the superficial area increase significantly, but more type II collagen was generated instead of type I collagen, which means that the cells repaired more hyaline cartilage instead of fibrous cartilage in the scaffold.
[0089] Therefore, the mechanism of action of the present invention is: taking osteoarthritis (OA) as an example, its main feature is that the structural degeneration and disorder of the extracellular matrix lead to the decline of lubrication effect in the joint and the increase of friction, and then the hypertrophy characteristics of healthy chondrocytes caused by stress stimulation appear, and the hypertrophic chondrocytes further secrete matrix enzymes (such as MMP13 and ADAMTS5), deepen the damage to the intra-articular environment, thereby forming a vicious circle; coupled with the fact that articular cartilage itself does not have the ability to repair, the consequences of this reciprocating will only be unimaginable. The present invention first plays the role of a buffer zone by introducing super-lubricating hydrogel in defective and diseased parts, alleviates the stress stimulation of the hypertrophic chondrocytes in the lesion, thereby inhibiting it from producing more matrix enzymes; meanwhile, the stem cells in the hydrogel scaffold gradually differentiate into healthy chondrocytes, and secrete abundant chondrocyte extracellular matrix (such as type II collagen and proteoglycans ...), on this basis, the original hydrogel scaffold will degrade in vivo therewith, and the degradation product (hyaluronic acid) is one of the important components in the intra-articular cartilage environment, and the product produced by the cells in the scaffold is exposed, reaching the effect of filling and repairing the defective structure at the lesion.
[0090] The present invention has the following beneficial effects:
[0091] The products and treatment technologies currently on the market are usually conservative, mainly focusing on relieving symptoms and temporarily improving joint function, and it is difficult to solve the problem of articular cartilage repair from the root. Existing technologies have limitations in treatment effects, and are usually unable to effectively achieve long-term repair, and cannot avoid the subsequent cartilage degeneration and recurrence problems. The super-lubricating three-dimensional biohydrogel based on stem cell therapy proposed in the present invention can fundamentally repair defects and lesions of articular cartilage, and has significant clinical significance.
[0092] Compared with the prior art, the present invention not only has excellent therapeutic effects, but also is relatively simple in design and manufacturing process, and the materials and reagents used are highly biocompatible. These materials can be safely degraded in the body and will not cause adverse reactions such as immune rejection and inflammation, thus ensuring the safety of the treatment process. Figure 8 and Fig. 9 As shown, the present invention verifies that the bioscaffold has excellent biocompatibility in animals (mouse model) based on the existing basic experimental data. In the osteochondral defect model, the scaffold can fit closely to the defect boundary, while promoting the accelerated growth of cells in the scaffold, and promoting the up-regulated expression of extracellular matrix (ECM) and lubricin (PRG4). At 4 weeks after surgery, the mouse osteochondral defect model has shown significant repair effects; in the longer 8 and 12 weeks, the repair effect is more obvious and lasting. At the same time, the super-lubricating hydrogel bioscaffold generates more type II collagen rather than type I collagen, which means that the cells generate more hyaline cartilage rather than fibrous cartilage in the scaffold.
[0093] Compared with existing treatment products on the market, although drug injection can quickly relieve pain and achieve therapeutic effects in a short period of time, due to the instability of the injection target and the gradual degradation of the drug, its effect will decay rapidly after reaching the peak, and the patient will soon return to the state before treatment, so it is necessary to repeatedly use this type of product to maintain a certain therapeutic effect. In contrast, the clinical efficacy of the present invention shows a trend closer to the change of an exponential function. With the gradual degradation of the stent in the body and the gradual increase in the secretion of the matrix by the cells, it can not only effectively relieve the patient's pain, but also fundamentally repair the lesion site to achieve a long-term healing effect. This feature makes the present invention far superior to existing market products in terms of therapeutic effect, with more lasting and stable clinical performance.
[0094] In general, the beneficial effects of the present invention are:
[0095] (1) Long-lasting efficacy: The course of treatment for drugs that prevent and relieve the pain of patients / customers through intra-articular injection is short, and the effect needs to be maintained by regular injection of the product. The present invention has corresponding effects in different stages of the entire efficacy. For example, during early implantation, its super-lubricating effect can effectively reduce the stress stimulation of chondrocytes at the lesion site and inhibit the production of more matrix enzymes; in the middle and late stages, the stem cells in the scaffold gradually differentiate into chondrocytes and begin to secrete chondrocyte matrix, accompanied by the gradual degradation of the original scaffold, which frees up more growth space for the newly differentiated chondrocytes and the newly secreted matrix, not only filling the defects at the lesion site, but also having mechanical properties that match the level of natural cartilage, so that the articular cartilage can be repaired as before. Therefore, the main advantage of the present invention is that it can fundamentally and thoroughly solve the problem once and for all, and its repair effect will become more and more obvious with the development of time until the properties of natural cartilage are restored.
[0096] (2) Commercialization: The materials used in the present invention are all approved by the FDA, have excellent biocompatibility, can be used for biological experiments and clinical applications, will not cause immune rejection or inflammatory response in the human body, and have low procurement costs. The processes involved, such as microfluidics, extrusion molding, ultrasonic fragmentation, or 3D bioprinting molding technology that may be involved, all have relatively mature systems in the current industrial market. Therefore, the product preparation cost of the present invention is low, the process is mature, and large-scale commercial production can be achieved. BRIEF DESCRIPTION OF THE DRAWINGS
[0097] Figure 1 The effect of OA on the size of cavities around chondrocytes; A is an example of the morphology of cavities (Lacuna) in healthy and osteoarthritis (OA) cartilage tissues; B is a quantitative analysis of the radial size of cavities in healthy and OA lesions;
[0098] Figure 2 Schematic diagram of the actual composition and application of superlubricating hydrogel scaffold and boundary layer lubrication effect (water shell effect);
[0099] Figure 3 A is the structure of phospholipid molecules; A is a schematic diagram of the three-dimensional structure of liposomes; B is a schematic diagram of three different types of liposomes, namely SUV, LUV, and MLV, according to their particle size;
[0100] Figure 4 The friction performance of three-dimensional biohydrogel scaffolds containing different concentrations of liposomes (0-100mM) was tested by mechanical performance testing instruments and the lubrication effect was significantly improved; A is the lateral force (friction force) and normal stress between each group recorded and converted into COF (friction coefficient) as shown in the figure; B is the relationship between COF and the concentration of liposomes mixed in the bioscaffold obtained by statistics;
[0101] Figure 5 The Young's modulus of three-dimensional biohydrogel scaffolds containing different concentrations of liposomes (0-100mM) was tested by a mechanical properties testing instrument and it was verified that the hardness of the hydrogel scaffold was close to the hardness of the matrix around chondrocytes, which was suitable for cell growth; A is the stress-strain curve obtained by recording stress and strain; B is the relationship between the statistically obtained Young's modulus and the concentration of liposomes mixed in the bioscaffold;
[0102] Figure 6 To transplant cells into the super-lubricating biohydrogel scaffold, the cells maintained a high survival rate (greater than 85%) after 7 days of in vitro culture at various liposome concentrations (0-100 mM);
[0103] Figure 7To transplant cells into the super-lubricating biohydrogel scaffold, cells secreted more chondrocyte extraplasmic matrix in the high liposome concentration group;
[0104] Figure 8 In order to construct an osteochondral defect model in mice, the control group loaded with cells and the experimental group of super-lubricating hydrogel scaffolds were injected into the defect. After 8 weeks of observation, it was found that the repair effect of the experimental group at the defect was significantly better than that of the control group; A is verified by hematoxylin-eosin staining (H&E), which verifies that the experimental group has a good fit with the native tissue and shows a significant repair effect; B is verified by Sudan red staining (Safranin-O), which verifies that the cells in the experimental group secreted more cartilage extracellular matrix, and the overall chondrogenic differentiation is more obvious;
[0105] Fig. 9 The immunohistochemical staining of PRG4 was performed on the 8-week mouse osteochondral defect model to detect the effect of lubrication on cells in the experimental group; A shows that the expression of PRG4 in the superficial layer of the experimental group was significantly higher than that of the defect and material control groups, and was close to the expression level of the SHAM group; B shows the negative control group without incubation of PRG4 antibody; DETAILED DESCRIPTION
[0106] In order to make the purpose, technical scheme and advantages disclosed in the embodiments of the present invention more clearly understood, the embodiments of the present invention are further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the embodiments of the present invention and are not intended to limit the embodiments of the present invention. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0107] Example 1
[0108] Preparation of macroscopic HAMA hydrogel scaffolds
[0109] 1g of sodium hyaluronate (HA) (molecular weight 100,000-200,000, product number H-0443571, HEOWNS, Tianjin, China) was dissolved in 100mL of aqueous solution. After fully dissolved, 1mL of methacrylic acid (product number: M-58350, HEOWNS, Tianjin, China) was added, and then the solution was placed in a 4°C environment and the pH was maintained at 8-8.5 for 12 hours. After sufficient reaction, the solution was placed in a dialysis tape (8000-14000 kDa) for dialysis. After two days, the dialysis was completed and freeze-dried to obtain HAMA powder.
[0110] The obtained HAMA powder was dissolved in PBS solution at 3% (w / v), and 0.1% (w / v) of photoinitiator (2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone) (Cat. No.: H137984, Aladdin, China) was dissolved in the above solution to form HAMA hydrogel precursor solution (Pre-hydrogel). After the solution was mixed uniformly by vortexing and ultrasound, the solution was subjected to ultraviolet light at a wavelength of 365 nm and 10 mW / cm 2 The HAMA hydrogel scaffold was formed by irradiating and curing under blue light for 5 minutes.
[0111] Example 2
[0112] Preparation of gelatin microspheres
[0113] Gelatin (300 bloom, type A, Sigma-Aldrich, USA) was dissolved in preheated distilled water (40-60°C), and dissolved in PBS at a concentration of 10% (w / v) to prepare a gelatin solution, stirred until completely dissolved, and the solution temperature was kept at 40-60°C to prevent gelatin from solidifying. Take an appropriate amount of mineral oil or vegetable oil, add an emulsifier (Span 80), stir evenly, and use it as a continuous phase (emulsifier concentration is 2%, volume ratio). The gelatin solution was injected into the dispersed phase channel of the microfluidic chip through a syringe pump, and the flow rate was controlled to be 30μL / min; the continuous phase was injected into the continuous phase channel of the chip through another syringe pump, and the flow rate was controlled to be 500μL / min. The volume of the continuous phase was 10 times the volume of the dispersed phase, ensuring that the size of the gelatin microspheres obtained later was about 50μm. After setting the above parameters, the gelatin solution will form uniform droplets (precursor of gelatin microspheres) in the microfluidic chip under the shearing action of the oil phase. The formed gelatin droplets are collected in a container containing the oil phase, and a low temperature (4°C) is maintained to avoid droplet fusion. In order to solidify the gelatin microspheres, the temperature is maintained at 4°C for a period of time. After the solidification reaction is sufficient, the microspheres are washed with ethanol several times to remove the excess oil phase. Finally, the microspheres are rinsed with distilled water and freeze-dried. The freeze-drying temperature is -40 to -20°C, the vacuum degree is below 200Pa, and the time is 20 hours to obtain dry gelatin microsphere powder.
[0114] Example 3
[0115] Preparation of nano-sized liposomes
[0116] Hydrogenated soybean phosphatidylcholine (HSPC) (Lipoid, GmbH, Germany) was dissolved in PBS to obtain a 100 mM HSPC phospholipid solution, and then the phospholipid solution was ultrasonically reacted under certain ultrasonic conditions (600 W, 15 minutes). After the ultrasonic reaction was completed, the prepared HSPC liposome suspension was obtained.
[0117] Sucrose is added to the prepared HSPC liposome suspension to a concentration of 5-10% (w / v) in the liposome suspension (the purpose of adding sucrose here is to protect the liposomes in the subsequent freeze-drying process). After mixing evenly, the liposome-sugar mixed solution is rapidly frozen. After rapid freezing, it is placed in a freeze dryer to obtain freeze-dried powder of HSPC liposomes.
[0118] Example 4
[0119] Construction of HAMA / Gel-lipo hydrogel scaffold
[0120] The HAMA freeze-dried powder obtained above was dissolved in PBS at a concentration of 3% (w / v) to obtain a HAMA hydrogel presolution, and then freeze-dried gelatin microspheres were added at a concentration of 10% (w / v), and HSPC liposome powder was dissolved in the HAMA hydrogel presolution at concentrations of 0, 10mM, 50mM and 100mM, respectively, and 0.1% (w / v) of a photoinitiator (2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone) was dissolved in the mixed solution, and then the solution was mixed evenly by vortexing and ultrasound to obtain a HAMA / Gel-lipo mixed solution containing four different concentrations of HSPC liposomes.
[0121] After mixing evenly, the obtained HAMA / Gel-lipo mixture was dripped into the mold and heated at a wavelength of 365nm, 10mW / cm 2 The HAMA / Gel-lipo hydrogel scaffold was formed by irradiating and curing under blue light for 5 minutes.
[0122] The friction performance of the HAMA / Gel-lipo hydrogel scaffold was tested using a mechanical performance testing instrument Mach-1 (Biomomentum, Canada). Using PBS as the liquid environment and a glass slide as the substrate, the hydrogel was repeatedly laterally displaced in this environment (lateral displacement: 20 mm, speed: 1 mm / s, number of repetitions: 3). The friction force (Ff) and normal stress (FN) generated by the hydrogel scaffold during the displacement were recorded by the mechanical sensor above, and then the formula was used:
[0123] Friction coefficient (μ) = (friction force (F_f)) / (normal stress (F_N));
[0124] The friction coefficient (μ) was used to characterize the lubrication performance of the hydrogel scaffold in a simulated biological liquid environment.
[0125] The results are as follows Figure 4As shown, the friction performance of the three-dimensional biohydrogel scaffold containing different concentrations of liposomes (10mM, 50mM and 100mM) was tested by a mechanical performance testing instrument and verified that the lubrication effect was significantly improved; (A) by recording the lateral force (friction force) and normal stress between each group, and converting them into COF (friction coefficient) as shown in the figure; (B) by statistically obtaining the relationship between the COF and the concentration of liposomes mixed in the bioscaffold. It is explained that when the present invention introduces liposomes into the bioscaffold, the lubrication effect of the overall scaffold is significantly improved, especially in the high concentration group (50mM and 100mM), the lubrication coefficient of both is significantly reduced compared with the control group, and the COF is close to the range of 0.003-0.02, which is very close to the level of natural cartilage (the COF of natural human articular cartilage is in the range of 0.003-0.02.).
[0126] The Young's modulus performance of the HAMA / Gel-lipo hydrogel scaffold was tested using the mechanical properties testing instrument Mach-1 (Biomomentum, Canada) in the compressive mode. The glass slide was used as the substrate, and the downward extrusion displacement of the hydrogel in this environment was recorded (lateral displacement: 80% of the height of the hydrogel scaffold, speed: 0.0167mm / s, number of repetitions: 3). The stress (σ) generated by the hydrogel scaffold during the displacement was recorded by the mechanical sensor above, and then the formula was used:
[0127] Young's modulus (E) = (stress (σ)) / (strain (ε));
[0128] Young's modulus (E) was used to characterize the hardness properties of the hydrogel scaffold in a simulated biological microenvironment.
[0129] The results are as follows Figure 5 As shown, the Young's modulus of the three-dimensional biohydrogel scaffold containing different concentrations of liposomes (0-100mM) was tested by a mechanical properties testing instrument and verified that the scaffold hardness was maintained in a relatively stable range (10-12kPa); (A) By statistically analyzing the relationship between the Young's modulus and the concentration of liposomes mixed in the bioscaffold, it can be seen that the Young's modulus data of the high concentration groups (50mM and 100mM) were significantly lower than those of the control group.
[0130] Example 5
[0131] Construction of HAMA / Gel-lipo cell / hydrogel scaffold
[0132] Before mixing stem cells, HAMA, gelatin microspheres and nanoliposomes, ensure that all reagents and operations in the following steps are performed under sterile conditions.
[0133] A certain amount of mesenchymal stem cells (MSC) were prepared, 10% (w / v) gelatin microspheres and cell suspension were fully mixed at a density of 500,000 cells / ml, and incubated at room temperature (25°C) for 4 hours to allow the cells to fully adhere to the gelatin microspheres. After the adhesion process was fully completed, HAMA was dissolved in the cell / gelatin microsphere mixture at a concentration of 3% (w / v), HSPC freeze-dried powder was dissolved in the cell / gelatin microsphere mixture at concentrations of 0, 10mM, 50mM and 100mM, and 0.1% (w / v) of photoinitiator (2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone) was dissolved in the mixed solution, and then the mixture was mixed evenly by vortexing and ultrasonication to obtain a HAMA / Gel-lipo / cell mixture.
[0134] After mixing evenly, the obtained HAMA / Gel-lipo / cell mixture was dripped into the mold and then heated at a wavelength of 365nm, 10mW / cm 2 After irradiation and curing under blue light for 5 minutes, the HAMA / Gel-lipo cell / hydrogel scaffold was formed.
[0135] HAMA / Gel-lipo cells / hydrogel scaffolds were cultured at 37°C and 5% CO 2 Under the environment of 40 °C, the culture medium was replaced every two days, and the cytotoxicity detection kit (L-3224, Life Technologies) was used for detection on the 7th day of in vitro culture. The method includes preparing a mixed solution of Calcein-AM and Ethidium homodimer-1 with concentrations of 0.5 μL / mL and 2 μL / mL, respectively. After washing the scaffold with PBS 7.4 buffer, the detection solution was added to the scaffold and incubated at 37 °C for 20 minutes. Fluorescence image detection was performed using a microscope (Nikon Ti2-E inverted fluorescence microscope). The fluorescent staining of live cells was detected using an excitation wavelength of 488 nm and appeared green. Dead cells were detected using an excitation wavelength of 633 nm and appeared red. The number of live and dead cells was manually counted, and the cell viability was calculated by dividing the number of live cells by the total number of cells, and analyzed using ImageJ software.
[0136] The results are as follows Figure 6 As shown, (A) fluorescent images of cell survival were taken between groups using a fluorescent microscope; (B) statistically analyzed the survival rate of cells after 7 days of in vitro culture. The results showed that the survival rate of cells in each group reached about 85%, indicating that the hydrogel scaffold of the present invention has excellent biocompatibility.
[0137] In vitro culture chondrogenesis experiment of HAMA / Gel-lipo cells / hydrogel scaffold
[0138] HAMA / Gel-lipo cells / hydrogel scaffolds were cultured at 37°C and 5% CO 2 Under the environment of 4% paraformaldehyde, the culture medium was replaced every two days. On the 14th and 21st days, the cultured cells / hydrogel scaffolds were removed, fixed in 4% paraformaldehyde for one day, and then placed in cryoembedding medium (OCT) for three days. The frozen sections were obtained by liquid nitrogen quick freezing and pathological morphological analysis (Alcian blue) was performed.
[0139] The results are as follows Figure 7 As shown, when cells were transplanted into the super-lubricating biohydrogel scaffold, the cells secreted more cartilage extraplasmic matrix in the high liposome concentration group.
[0140] Osteochondral defect repair experiment of HAMA / Gel-lipo cells / hydrogel scaffold
[0141] In order to verify the repair effect of the hydrogel scaffold in vivo when co-cultured with cells, the present invention constructed a mouse osteochondral defect model (refer to the prior art Wang, J., Zhang, F., Tsang, WP, Wan, C., & Wu, C. (2017). Fabrication of injectable high strength hydrogel based on 4-arm star PEG forcartilage tissue engineering. Biomaterials, 120, 11-21.), and the pathological tissue sections proved that the model constructed a defect with a length of 1 mm and a depth of 1 mm at the distal end of the femur of SCID mice, indicating that the model was successful. After the construction was completed, we took 1 μL of the HAMA / Gel-lipo / cell mixture in Example 5 and dripped it into and covered the defect, and then used a wavelength of 365 nm, 10 mW / cm 2 The cells were irradiated and cured under blue light for 5 minutes. After curing, they were sutured and the mice were observed and cultured for 4 and 8 weeks.
[0142] After the expiration, the osteochondral tissue of the sacrificed mice was removed and embedded in paraffin. The implantation site of the hydrogel scaffold was found through paraffin sectioning, and then pathological morphological analysis was performed. The cell morphology and the adhesion to the surrounding tissue were observed and analyzed by hematoxylin-eosin staining, and the content of extracellular matrix (chitosan, glycosaminoglycan) secreted by the cells was detected by safranin-O staining. The corresponding antibodies (such as PRG4, Col II and MMP13) were selected to perform immunohistochemical analysis on the model to verify its repair effect on osteochondral defects.
[0143] The experimental steps of hematoxylin-eosin (H&E) staining are as follows:
[0144] Put the slices in xylene, anhydrous ethanol, 90% alcohol, 80 alcohol for 5 minutes, and 70% alcohol for 2 minutes each, and finally rinse with tap water to complete the dewaxing process. Then put the dewaxed slices in hematoxylin stain for 3-5 minutes, then rinse with tap water, observe the staining under the microscope, if the color is darker, rinse with tap water appropriately, if the color is lighter, continue to restain until the color is appropriate; then put it in eosin stain for 0.5-1 minute. After completing the two stainings, put the slices in 70% alcohol, 80 alcohol, 90% alcohol and xylene for 2 minutes each, and finally seal the slices.
[0145] The staining results in blue nuclei and red cytoplasm, which can help clearly display the morphological structure of cells and tissues.
[0146] The experimental steps of Safranin-O staining are as follows:
[0147] The sections were placed in xylene, anhydrous ethanol, 90% alcohol, 80 alcohol for 5 minutes, and 70% alcohol for 2 minutes each, and finally rinsed with tap water to complete the dewaxing process. Then the sections were stained in Weigert's iron hematoxylin solution for 5 minutes. Differentiation was performed using acidic ethanol differentiation solution for 15 seconds; then washed with distilled water for 1 minute; immersed in fast green staining solution for 1-2 minutes, and washed with distilled water for 1 minute. The sections were immersed in safranin-O staining solution for 5 minutes and washed with distilled water for 1 minute. After staining, the sections were placed in 70% alcohol, 80 alcohol, 90% alcohol and xylene for 2 minutes each, and finally sealed. The staining results showed that the cartilage matrix was red, the chondrocyte nucleus was blue, the cytoplasm, muscle, collagen fiber and bone tissue were gray-green, the chondrocyte cytoplasm was red, and the nucleus was gray-black.
[0148] The experimental steps of immunohistochemical staining (PRG4) are as follows:
[0149] The sections were placed in xylene, anhydrous ethanol, 90% alcohol, 80 alcohol for 5 minutes, and 70% alcohol for 2 minutes, and finally rinsed with tap water to complete the dewaxing process. Antigens were repaired by heat-mediated method, specifically by placing the sample in a solution of 10mM sodium citrate, 0.05% Tween 20, pH 6.0, and maintaining it at 98°C for 20 minutes to achieve antigen repair. After taking out the sample, use blocking solution (such as serum, protein, etc.) to block non-specific binding sites to reduce background staining; incubate the specific first antibody Anti-Lubricin / MSF (ab28484, abcam) with the antigen on the tissue section to allow the antibody to fully bind to the antigen, generally at room temperature for 4 hours or 4°C overnight; use a second antibody with a marker (such as an enzyme) (IHC kit, ab269452, abcam) to bind to the first antibody to prepare for the color development step; form a visible color signal on the tissue section through an enzyme substrate reaction (such as DAB) to show the location and expression level of the antigen; use hematoxylin as a counterstain to better locate protein expression; finally, seal the section and observe.
[0150] The results are as follows Figure 8 , Fig. 9 shown. Figure 8 In the figure, (A) Hematoxylin-eosin staining (H&E) verified that the experimental group had good adhesion to the native tissue and showed a significant repair effect; (B) Sudan red staining (Safranin-O) verified that the cells in the experimental group secreted more cartilage extracellular matrix, and the overall chondrogenic differentiation was more obvious. The results showed that by constructing an osteochondral defect model in mice, the control group loaded with cells and the experimental group of super-lubricating hydrogel scaffolds were injected into the defect. After 8 weeks of observation, it was found that the repair effect of the experimental group at the defect was significantly better than that of the control group.
[0151] Fig. 9 To detect the effect of lubrication on cells in the experimental group by immunohistochemical staining of PRG4 in an 8-week mouse osteochondral defect model; (A) The expression of PRG4 in the superficial layer of the experimental group was significantly higher than that of the defect and control groups, and was close to the expression level of the SHAM group; (B) Negative control group without incubation of PRG4 antibody.
[0152] Comparative Example 1
[0153] On the basis of Example 5, the gelatin in Example 2 was replaced with an equal molar amount of double bond gelatin (GelMA), and the prepared double bond gelatin microspheres replaced an equal amount of gelatin microspheres, and HSPC freeze-dried powder was added at a concentration of 50 mM to prepare the cell / hydrogel scaffold of Comparative Example 1.
[0154] Using it for the same performance test, the results show:
[0155] When the gelatin microspheres were replaced with an equimolar amount of GelMA microspheres, the hydrogel scaffold was physically characterized and tested. The results showed that the overall Young's modulus of the hydrogel was slightly improved (the structure of the scaffold microenvironment was denser), but the COF of the scaffold did not change significantly compared with the hydrogel scaffold in the present invention.
[0156] After three-dimensional culture in vitro, the results showed that the bioscaffold with GelMA microspheres showed strong biocompatibility, and the stem cells showed obvious proliferation in the scaffold. However, subsequent observations and tests found that after replacing gelatin with GelMA, the cells did not show obvious aggregation or suspended growth, and were more inclined to grow along the wall. Through further observation and analysis, it was found that in the bioscaffold with GelMA microspheres, compared with the hydrogel of the present invention, the stem cells did not show the unique morphology of chondrocytes (elliptical), but instead showed the characteristics of osteoblasts (flat polygonal shape); through staining of the extracellular matrix, it was also found that the stem cells attached to GelMA secreted less cartilage extracellular matrix (type II collagen, proteoglycans...) during growth, but the extracellular matrix of osteoblasts (type I collagen, osteonectin) increased significantly.
[0157] The above results show that when gelatin microspheres are replaced with GelMA, the Young's modulus of the overall bioscaffold will be slightly improved because the internal structure becomes dense, but the COF does not change significantly compared to the hydrogel scaffold of the present invention; there is no significant difference in the growth and proliferation of stem cells, but there is a significant effect on the differentiation of stem cells. In the presence of the hydrogel of the present invention, stem cells will have a significant differentiation towards the cartilage phase, but when gelatin is replaced with GelMA, the cells are more inclined to differentiate towards the osteogenic phase.
[0158] Comparative Example 2
[0159] The method of the prior art CN18178734B is referred to to prepare a macro-micro composite hydrogel scaffold, comprising:
[0160] S1. Preparation of GelMA micro-hydrogel scaffolds
[0161] (1) Prepare a 0.5 g / mL GelMA solution with deionized water, add 3 wt % phenyl (2,4,6-trimethylbenzoyl) phosphate lithium salt, and transfer the solution into one of the syringes of a microinjection pump, which is recorded as the water phase.
[0162] Take 40 mL of olive oil (containing 35% Span80 by volume) and transfer it into another syringe of the microinjection pump, which is recorded as the oil phase.
[0163] (2) The aqueous phase and the oil phase were injected at a rate of 0.4 mL / h and 120 mL / h, respectively, so that they intersected in the T-shaped channel of the injection needle, generating shear force to produce GelMA microgels.
[0164] The microgel was collected in a small glass bottle containing an oil phase and cured under UV light at 365 nm, 180 mW / cm' for 30 s. After standing, the upper oil phase was removed by aspiration and the microscopic hydrogel, i.e., the microgel, was washed with acetone for several times to obtain the microscopic hydrogel. The microgel was freeze-dried and set aside.
[0165] S2, Rhodamine B red fluorescence labeled microgel GelMA
[0166] (1) 0.15 g of rhodamine B was dissolved in 10 mL of N,N-dimethylformamide, followed by the addition of 0.2 g of N-hydroxysuccinimide and 0.2 g of 1-ethyl-3-dimethylaminopropyl-carbodiimide hydrochloride, stirring to dissolve, and reacting at room temperature for 4 h. This was recorded as the activation solution.
[0167] (2) Take 1g of GelMA microgel and dissolve it in 20mL of deionized water, heat it in a water bath, stir it magnetically, add 3mL of activation solution, react it in the dark for 24h, and add 80mL of deionized water to terminate the reaction. Put the above solution into a dialysis bag and dialyze it against deionized water (in the dark). The dialyzed solution is centrifuged to remove the precipitate, and the supernatant is transferred to a culture dish and freeze-dried to obtain rhodamine-labeled microgel.
[0168] S3. Construction of macro-micro composite hydrogel scaffolds
[0169] Fifty freeze-dried GelMA microgels were added to an aqueous solution with a total mass concentration of HAMA and GelMA of 6wt%, and 2wt% LAP blue light initiator was added. The mixture was shaken and mixed to obtain a composite solution. The composite solution was dropped into a mold and gently stirred with an injection needle to make the GelMA microgels evenly dispersed in the gel-making solution. The solution was irradiated and cured under blue light of 405nm, 10mW / cm* for 30s to form a macro-micro composite hydrogel scaffold.
[0170] Using it for the same performance test, the results show:
[0171] By performing physical characterization tests on the above hydrogel, we found that the COF (μ is 0.08-0.2) of the hydrogel scaffold is significantly higher than that of the hydrogel scaffold of the present invention, and is much higher than the value of natural cartilage (μ value is 0.002-0.03).
[0172] After three-dimensional in vitro culture, the results show that the hydrogel bioscaffold of comparative example 2 exhibits strong biocompatibility, and the stem cells maintain a high survival rate in the scaffold, and significant proliferation can be observed. However, when the number of days of culture is extended to 14 and 21 days, the cells do not show obvious aggregation or suspension growth trends, but tend to grow by adhering to the wall; after further pathological detection and analysis of the bioscaffold, the results show that the cells in the bioscaffold do not show the unique morphology of chondrocytes (elliptical), but the characteristics of osteoblasts (flat polygonal shape) appear; by staining the extracellular matrix, it is also found that the stem cells in the hydrogel of comparative example 2 secrete less cartilage extracellular matrix (type II collagen, proteoglycans...) during growth. Specific immunohistochemical staining was performed on PRG4 related to cartilage surface lubrication, and the results showed that, compared with the present invention, PRG4 showed a significant downward trend, but the extracellular matrix (type I collagen, osteonectin) of osteoblasts was significantly increased.
[0173] The results showed that the hydrogel in Comparative Example 2 can significantly promote the differentiation of stem cells toward the osteogenic phase and secrete more extracellular matrix related to osteogenesis, but it cannot promote the differentiation of stem cells toward the cartilage phase like the hydrogel of the present invention, and cannot induce cells to express more chondrocyte-related extracellular matrix. Therefore, the hydrogel in Comparative Example 2 is not suitable for articular cartilage repair.
[0174] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A three-dimensional biohydrogel, characterized in that: The raw materials include, by weight: 1-5 parts of methacrylic anhydride hyaluronic acid HAMA, 0.05-0.15 parts of initiator, 3-8 parts of hydrogenated soybean phosphatidylcholine liposome and 7-13 parts of stem cell solution; The preparation method of the stem cell solution is as follows: gelatin and water are mixed to prepare a gelatin solution; the mixture is stirred evenly at 40-60° C. to prepare a dispersed phase; an emulsifier is added to the oil to prepare a continuous phase; the dispersed phase and the continuous phase are prepared by microfluidic technology to obtain uniform droplets, and the droplets are freeze-dried to obtain gelatin microspheres; Add 5*10 5 / mL of stem cells, incubate at 25-37°C for 2-4h to obtain a stem cell solution.
2. The three-dimensional biohydrogel according to claim 1, characterized in that: The mass concentration of gelatin in the gelatin solution is 5%-10%.
3. The three-dimensional biohydrogel according to claim 1, characterized in that: In the process of preparing uniform droplets by microfluidic technology, the flow rate of the dispersed phase is 30-40 μL / min; the flow rate of the continuous phase is 500-600 μL / min.
4. The three-dimensional biohydrogel according to claim 1, characterized in that: The particle size of gelatin microspheres is less than 65 μm.
5. A method for preparing the three-dimensional biohydrogel according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1, adding an initiator to methacrylic anhydride hyaluronic acid HAMA to obtain a hydrogel precursor solution; S2. Add hydrogenated soybean phosphatidylcholine liposomes and stem cell solution to the hydrogel precursor liquid, mix well, and obtain a composite solution; transfer the solution to a mold, and form a three-dimensional biohydrogel by photocuring.
6. The method according to claim 5, characterized in that The preparation method of the methacrylic anhydride hyaluronic acid HAMA is as follows: In a dark environment, equal masses of methyl methacrylate and hyaluronic acid are mixed evenly on ice, reacted for 10-14 hours, and the pH is maintained at 8-8.
5. The obtained solution is dialyzed and freeze-dried to obtain methacrylic anhydride hyaluronic acid HAMA.
7. The method according to claim 6, characterized in that The molecular weight of the hyaluronic acid is 100,000-200,000.
8. The method according to claim 5, characterized in that The hydrogenated soybean phosphatidylcholine liposomes are first dispersed and then added dropwise into the hydrogel precursor solution.
9. The method according to claim 5, characterized in that Light curing is at 365nm, 8mW / cm 2 -12mW / cm 2 Curing under blue light for 4-8 minutes.
10. Use of the three-dimensional biohydrogel according to any one of claims 1 to 4 in preparing a preparation for cartilage repair.
Citation Information
Patent Citations
Self-renewal hydrated lubricating drug-loaded hydrogel microspheres, preparation method and application thereof
CN113995891A
Preparation of stem cell and hydrogel combined biological material and application of stem cell and hydrogel combined biological material in spinal cord injury
CN115501253A
Preparation method and application of 3D stem cell loaded composite hydrogel
CN118178734A
Hydrogel microspheres and preparation method thereof
CN118304252A
Injectable porous composite bone repair hydrogel material based on thermally-induced sacrifice template method and preparation method of injectable porous composite bone repair hydrogel material
CN118697941A